One fact from the activity of rector KHIPE A.-B. P. Psheborsky: the role of personality in extreme life conditions. - Levchenko , Valeriy (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
Purpose: on the basis of archival historical sources introduced into scientific circulation for the first time, to add little-known facts to the history of the everyday life of representatives of the academic community of the Kharkiv Institute of Public Education (KHIPE) in 1922, to represent the figure of the rector of KHIPE, professor of mathematics A.-B. P. Psheborsky as a leader in overcoming difficult life situations in the early 1920s, which was determined by his certain personal qualities and constructive behavior, which contributed to the achievement of significant life goals in the conditions of uncontrolled life circumstances against the background of socio-political and socio-economic collapse.Research methodology: the principles of historicism and objectivity, embodied by the use of special historical methods – chronological and retrospective.Scientific novelty. For the first time, information about the address of the rector of KHIPE A.-B. P. Psheborsky in the conditions of the famine of 1921–1922 to the «Nansen mission» with a request to provide material and financial assistance to representatives of the academic environment (teachers, graduate students, students, technical staff) of higher education, supplemented by the biography of A.-B. P. Psheborsky, one of the facts of the last year of his stay in Kharkiv before moving to Poland in 1922, the role of his personality in the formation of a constructive strategy for overcoming the critical circumstances of the lives of colleagues and subordinates in extreme living conditions is considered.Topicality. Supplementing the scientific biography of prominent cultural figures is always an important topic of historical research. 2023 marks the hundredth anniversary of the tragic events of the famine of 1921–1923, which befell all sections of the USSR, including representatives of the academic community. Supplementing with new documentary facts of complex events of that time is an interesting and relevant topic. An important point is tracing the careful attitude towards the fate of subordinates on the part of the management of one of the leading universities of Kharkiv in the person of A.-B.  P. Psheborsky.Conclusions. Little-known pages of the biography of the rector of KHIPE, professor of mathematics A.-B. P. Psheborsky. On the basis of represented historical sources, it was possible to reproduce some facts of his last year of life in Kharkiv. The continuation of the search, development and introduction into scientific circulation of new materials concerning the fate of the representatives of the academic corporation in the conditions of the tragic events of 1921–1923 will reveal and supplement the essence of those terrible events even more fully. The study and popularization of documents that vividly demonstrate how, thanks to the help of the «Nansen’s Mission», a large number of the population of the USSR managed to survive, should be brought to wide circles of the public.